[ATTACH=full]3582[/ATTACH] [ATTACH=full]3583[/ATTACH] [ATTACH=full]3584[/ATTACH]

correction: ln(x)=t ln(y)=u 1. ln(ex/y)-ln(y/(ex)..........use quotient rule ln(ex)/ln(y)-ln(y)/ln(ex).......use product rule (ln(e)+ln(x))/ln(y)-ln(y)/(ln(e)+ln(x))............ln(e)=1 (1+ln(x))/ln(y)-ln(y)/(1+ln(x))...........substitute given ln(x)=t and ln(y)=u (1+t)/u-u/(1+t) (t^2 + 2 t - u^2 + 1)/((t + 1) u) 2. ((ln(x))^3-ln(x^4))/((ln(x/e^2))*ln(xe^2)) =(t^3-4ln(x))/((ln(x)-2ln(e))*(ln(x)+2ln(e))).........substitte given ln(x)=t and ln(y)=u =(t^3-4t)/((t-2*1)*(t+2*1)) =(t(t^2-4))/((t-2)*(t+2)) =(t(t-2)(t+2))/((t-2)*(t+2)).......simplify =t